Empowering Rural Farmers through Digital Entrepreneurship and Marketing Training in Pancakarya, Karawang, Indonesia - Fenina Berliana Putri; Wiwin Lestari; Aliman, Aliman; Pupung Purnamasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This community service program was implemented in Pancakarya Village, Tempuran District, Karawang Regency, with the aim of enhancing farmers' capacity in entrepreneurship and digital marketing. The primary challenges faced by the village community include limited understanding of business management, dependence on middlemen, and a lack of digital technology utilization in agricultural product marketing. To address these issues, the program provided training on fundamental entrepreneurial principles, financial recording, digital marketing strategies, and the use of e-commerce platforms and social media using lecture and discussion method. The results indicate an improvement in the community's understanding of business management and digital marketing strategies. Some participants have begun implementing digital marketing techniques, although challenges such as limited digital literacy and restricted internet access remain obstacles. Initial evaluations show that the program has contributed to raising awareness of the importance of diversifying marketing strategies to expand market reach and increase product value. Continued program support through intensive mentoring and collaboration with external stakeholders is necessary to ensure long-term impact and sustainability. With a comprehensive approach, this program is expected to foster economic independence in the village community through the effective utilization of digital technology.